Pengujian Usability Pada Prototype Aplikasiwadaya Dengan Metode Usability Testing Mengadopsi Standar Iso 9241:11 - Kadek Krisna; I Ketut Resika Arthana; Gede Aditra Pradnyana (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2019)
The purpose of this research is to test the usability of Wadaya application prototype using usability testing method adopting ISO 9241: 11 standard. Wadaya application prototype will be tested using three usability concepts namely effectiveness, efficiency, and user satisfaction. In this research, testing will be done twice with 20 respondents. The first prototype test result shows that (1) Wadaya application prototype is still not effective seen from mistakes made by respondents when during the execution of the task. The results showed 53.57%. (2) Wadaya application prototype is not efficient seen from the result of 44% Overall Relative Efficiency. (3) Wadaya application prototype has not fulfilled user satisfaction seen from 59,00 SUS score. The second prototype test results show that (1) Wadaya application second prototype is still not effective seen from mistakes made by respondents when during the execution of the task. The results showed 19,17% for the beginner group and 25,00% for the advance group. (2) Wadaya application second prototype is not efficient seen from the result of 74% Overall Relative Efficiency. (3)Wadaya application second prototype has fulfilled the user satisfaction seen from SUS score of 69,00 which is stated have satisfied when compared with SUS standard that is 68.